Text / Relational Database Management Systems: Harmonizing SQL and SGML - Tompa, F.W.; Blake, G.E.; Consens, M.P.; Kilpelainen, P.; Larson, Paul; Snider, T. (Springer-Verlag, 1994)
Combined text and relational database support is increasingly recognized as an emerging need of industry, spanning applications requiring text fields as parts of their data (e.g., for customer support) to those augmenting primary text resources by conventional relational data (e.g., for publication control). In this paper, we propose extensions to SQL that provide flexible end efficient access to structured text described by SGML. We also propose an architecture to support a text/relational database management system as a federated database environment, where component databases are accessed via "agents": SQL agents that translate standard or extended SQL queries into vendor-specific dialects, and text agents that process text sub-queries on full-text search engines.